Cultivating a Professional Culture of Peace and Inclusion: Conceptualizing Practical Applications of Peace Leadership in Schools - McIntyre Miller, Whitney; Abdou, Annmary S. (Frontiers in Education, 2018)
Beyond the role of educating students across all academic domains, school leaders are tasked with the monumental responsibility of creating positive, engaged systems and cultures that embrace the growing cultural, economic, linguistic and cognitive diversity in the United States landscape. With collective goals to create peaceful learning environments with capacity to serve diverse learners, many school leaders have embraced school-wide prevention and intervention efforts, such as Multi-Tiered Systems of Support (MTSS) for social-emotional and behavioral development of students. Unfortunately, due to the inherent complexities and fragmentation of such efforts, many school leaders have continued to experience significant barriers to sustainable systems change. Throughout the following discussion, the authors argue that the school-wide programs most commonly utilized in schools lack the explicit organizational structures for integrating culturally responsive practice, leadership development, and collaborative community building processes that are essential to sustainable implementation. Therefore, this conceptual paper aims to explore the possibilities for practical applications of the Integral Perspective of Peace Leadership (IPPL; McIntyre Miller and Green, 2015) within school systems change efforts by shifting focus from direct student skill development toward a more integrated and systems-oriented approach aimed at strengthening culture and capacity within communities of educational leaders. The IPPL can “connect the dots” and provide a strong foundation through which school-wide change is possible and more sustainable. By challenging individuals, schools, communities, and organizations to examine and include Innerwork; theories, behaviors and practices, or Knowledge building; Communities of practice; and Environment work, such as systems and global thinking (McIntyre Miller and Green, 2015), the implementation of the IPPL may “challenge issues of violence and aggression and build positive, inclusive social systems and structures” (McIntyre Miller, 2016, p.223). The purpose of this paper is twofold. First, there is a discussion of how the elements of the IPPL connect to school culture and system change. Second, specific examples, such as character development, mindfulness, school-wide positive behavior supports, social-emotional learning, professional learning communities, home-school connection, systems thinking, and distributed leadership, will demonstrate how school leaders might engage, using consultants and an implementation team, in the work to create positive, equitable school cultures.